Impact Of Knowledge Transfer/Sharing During The Period Of Uncertainty: Case Study On Industrial Downsizing - Nuril, Kusumawardhani (2007)
This project focuses on the impact of the downsizing on the knowledge sharing environment in Malaysia Airlines System Berhad (MAS). The method of this project was based on Grounded Theory and using closed setting interview for the further data collection at Malaysia Airlines Academy.